2002
DOI: 10.1152/ajpheart.2002.282.1.h87
|View full text |Cite
|
Sign up to set email alerts
|

Brachial artery dilatation responses in healthy children and adolescents

Abstract: To characterize brachial artery flow-mediated dilatation (FMD) in children, we monitored arterial diameter changes with ultrasound between 40 and 180 s after a 4.5-min forearm cuff occlusion-induced hyperemia in 105 healthy children (mean age, 11 yr; range, 9-16 yr). The peak FMD was 7.7 +/- 4.0% and occurred 79 +/- 33 s after cuff release. FMD at 60 s (5.3 +/- 4.0%) was significantly lower than the peak FMD (P < 0.0001). Twenty-three percent of the children (n = 24) reached peak FMD first after 110 s of posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
73
2
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 23 publications
13
73
2
5
Order By: Relevance
“…This finding agrees with other studies that reported a relationship between serum cholesterol, endothelial dysfunction, and intimal-medial thickness (13,14).…”
Section: Discussionsupporting
confidence: 93%
“…This finding agrees with other studies that reported a relationship between serum cholesterol, endothelial dysfunction, and intimal-medial thickness (13,14).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the timing of the measurement after cuff deflation may explain our negative result. Järvisalo et al (22) has found a great variation in the FMD as a function of the time after cuff deflation in healthy children. We chose to delay the measurement until 80-90 s after deflation to identify the late responders also, but the relatively large SD of the FMD may result from the variance in the response time in our patients.…”
Section: Discussionmentioning
confidence: 97%
“…We chose to delay the measurement until 80-90 s after deflation to identify the late responders also, but the relatively large SD of the FMD may result from the variance in the response time in our patients. Continuous registration of the vessel diameter from 30 to 150 s is recommended to overcome the problem of the individual variation in FMD (22).…”
Section: Discussionmentioning
confidence: 99%
“…14,15 There are no other studies on medical literature indexes that define standards for normal endothelial function in adolescents.…”
Section: Methodsmentioning
confidence: 99%